Health-related quality of life in children with PFAPA syndrome - Grimwood, Claire (Orphanet J Rare Dis, 2018)
BACKGROUND: Conventionally, PFAPA syndrome is considered as a benign disease compared to other recurrent fevers because it completely passes before adulthood. However, in our clinical practice, fever episodes have a huge impact on daily activities. METHODS: Observational cohort study using the Pediatric Quality of Life Inventory (PedsQL™ 4.0) Generic Core and Fatigue Scales. PedsQL™ uses a modular approach to measure the HRQOL in children with acute and chronic health conditions. We used pediatric FMF patients as the control group. RESULTS: We included 33 children with PFAPA and compared them to 27 FMF patients matched for age: preschool-age children (2 to 7 years) and school-age children and youths (8 to18 years). PedsQL™ self-reported scores of children with PFAPA were systematically lower than those of FMF peers for general quality of life and physical and psychosocial functioning (significant only in the preschool-age group). PedsQL™ self-reported fatigue scores of children with PFAPA were significantly lower than those of FMF peers for both preschoolers and school-age children and youths. Parent proxy-reports were not significantly different, even though scores were systematically lower for the parents of PFAPA children. CONCLUSION: Our study demonstrates, for the first time, that the wellbeing of PFAPA children is poor, with a major impact on psychosocial functioning and increased fatigue. The quality of life of PFAPA children appears to be even lower than that of FMF patients, for whom a lower than normal HRQOL has already been demonstrated.